Discourse Of Electronic Evidence-Based Police Investigation In The Era Of Digital Transformation - Famudin, Famudin (JURNAL LEGALITAS, 2023)
This study explores the integration of electronic evidence in criminal investigations within the Gorontalo Police Women and Children Protection Unit (PPA), examining the challenges and implementation in the digital era. The research uses an empirical legal approach, gathering primary data through interviews and secondary data from literature and legal texts. The study finds that while Indonesian laws—such as Law No. 02 of 2002 concerning the National Police, Law No. 8 of 1981 concerning Criminal Procedure Code (KUHAP), and Law No. 19 of 2016 concerning Electronic Information and Transactions—support the use of electronic evidence, the internal Standard Operating Procedures (SOPs) for investigating crimes based on digital data remain unclear. Primary challenges include inadequate SOPs, limited human resources, insufficient budgets, and a lack of necessary facilities and infrastructure. Furthermore, there is a high degree of sectoral ego, both within the community and among government agencies like the Office of Communication and Information, which complicates the coordination needed for effective electronic-based investigations. This study highlights the need for clearer guidelines and better resource allocation to fully leverage electronic evidence in criminal justice processes.